1999
DOI: 10.1074/jbc.274.8.4702
|View full text |Cite
|
Sign up to set email alerts
|

Transactivation of the Urokinase-type Plasminogen Activator Receptor Gene through a Novel Promoter Motif Bound with an Activator Protein-2α-related Factor

Abstract: The urokinase receptor overexpressed in invasive cancers promotes laminin degradation. The current study was undertaken to identify cis elements and trans-acting factors activating urokinase receptor expression through a footprinted (؊148/؊124) region of the promoter containing putative activator protein-2-and Sp1-binding motifs. Mobility shifting experiments using nuclear extract from a high urokinase receptorexpressing cell line (RKO) indicated that Sp1, Sp3, and a factor similar to, but distinct from, activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
52
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 49 publications
(49 reference statements)
6
52
0
Order By: Relevance
“…The same was observed for a promoter construct mutated for the binding of the AP-2-like transcription factor, described in a previous work (Allgayer et al, 1999c), and Sp1/Sp3 simultaneously ( Figure 4b, lanes 5 and 9). In addition, a u-PAR promoter construct deleted for region À148/À124 unable to bind the AP-2-like protein, Sp1 and Sp3 was not inhibited by pdcd4 expression in contrast to the wild-type u-PAR promoter ( Figure 4c, lanes 4 and 5).…”
Section: Pdcd4 Regulates Invasion and U-par Expressionsupporting
confidence: 87%
See 4 more Smart Citations
“…The same was observed for a promoter construct mutated for the binding of the AP-2-like transcription factor, described in a previous work (Allgayer et al, 1999c), and Sp1/Sp3 simultaneously ( Figure 4b, lanes 5 and 9). In addition, a u-PAR promoter construct deleted for region À148/À124 unable to bind the AP-2-like protein, Sp1 and Sp3 was not inhibited by pdcd4 expression in contrast to the wild-type u-PAR promoter ( Figure 4c, lanes 4 and 5).…”
Section: Pdcd4 Regulates Invasion and U-par Expressionsupporting
confidence: 87%
“…We previously reported that u-PAR gene expression in cultured colon cancer is largely due to a transcriptional activation of the gene, and diverse cis-elements of the u-PAR promoter were characterized as being essential for this regulation (Wang et al, 1994;Lengyel et al, 1996;Allgayer et al, 1999c). We, therefore, asked as to whether Pdcd4 is able to regulate u-PAR gene expression at the promoter level.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations